Teatro de grupo: utopia e realidade de uma existência no tempo - Melo, Flávio Vieira de (Universidade Federal de São Carlos, 2019)
The aim of this work was to look at the conflicts of a street theatre ensemble based in Sorocaba. Away from São Paulo, the ensemble did not go through the marketing's pressures of the capital and persevered over the sixteen years of existence. The cornerstones of this study are the moment which the ensemble was stablished, the organisational and contextual necessity of Sorocaba, the city’s public politics of cultural fundings, the ensemble's militancy and theatre pedagogy. Due to my immersion in this work, I came across protocols, reviews and clippings. Furthermore, it enables me to identify a curios core element for the survival of the theatre ensemble, in its own purpose for “theatre’s Decentralisation and popularisation”. The ensemble’s engagement to create an identity generated the elaboration of a examination, which even in the challenging and substandard moments, made it possible to recover and alter their work. Consequently, contributing to their permanence. This research was done based on interviews, essays, my daily participation within the ensemble and other documents; which suddenly brought the aspects that composes the existence of the street theatre ensemble. Looking globally at the proposed research, it becomes singular the Study Case in Nativos Terra Rasgada ensemble, using a Qualitative Methodology.
Group theater: Utopia and reality of a timeless existence
Keywords: Teatro de rua; Teatro de grupo; Sobrevivência; Existência; Resistência; CIENCIAS HUMANAS::EDUCACAO